Architectural Meaning in Hebraic Measurement and Orientation - Stanley Tigerman (Oz, 1996)
When the great 19th Century architect Louis H. Sullivan uttered the phrase "Form Follows Function," little did he realize just how literally he would be taken by the majority of descendant American architects. In just three little words, he deprived architecture of form emanating from any source other than the use to which it would be put.